2019
DOI: 10.1177/2325967119859518
|View full text |Cite
|
Sign up to set email alerts
|

The WORC Index and Predicting Treatment Failure in Patients Undergoing Primary Arthroscopic Rotator Cuff Repair

Abstract: Background: Rotator cuff tears are common injuries that are reliably treated with arthroscopic repair, producing good to excellent results. The Western Ontario Rotator Cuff (WORC) index is a validated disease-specific instrument used to assess patient outcomes; however, no study to date has correlated WORC index with treatment failure. Purpose: To evaluate the WORC index as a predictor for successful treatment in arthroscopic rotator cuff repair. An additional purpose was to identify patient and tear character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…While some evidence has suggested that obesity, diabetes, and smoking status may impair tendon healing, 18,20,35 only half of the studies that evaluated these risk factors found an association with revision surgery. Of note, the study of Herring et al 22 showed trends consistent with the larger studies included in this review but was likely underpowered to detect significant differences with only 28 cases of failure in the sample. For example, 52% of failure cases had a smoking history compared with 40% of treatment success cases, and 22% of failure cases had diabetes compared with 8% of success cases.…”
Section: Discussionmentioning
confidence: 61%
“…While some evidence has suggested that obesity, diabetes, and smoking status may impair tendon healing, 18,20,35 only half of the studies that evaluated these risk factors found an association with revision surgery. Of note, the study of Herring et al 22 showed trends consistent with the larger studies included in this review but was likely underpowered to detect significant differences with only 28 cases of failure in the sample. For example, 52% of failure cases had a smoking history compared with 40% of treatment success cases, and 22% of failure cases had diabetes compared with 8% of success cases.…”
Section: Discussionmentioning
confidence: 61%
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%
“… Unique analyses ∗ (n = 73) No. (%) Associated references Objective outcomes 14 (19) 31 , 43 , 44 , 45 Muscle strength 7 (9.5) 31 , 43 , 45 Range of motion 7 (9.5) 43 , 44 , 45 Patient-reported outcome measures 59 (81) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 47 American Shoulder and Elbow Surgeons score 16 (22) 25 , 26 , 27 , 29 , 30 , 31 , 33 , 36 , 37 , 42 , 46 , 47 Shoulder pain …”
Section: Resultsmentioning
confidence: 99%
“…Few studies have reported concomitant SSC lesion as a risk factor for failure; however, Herring et al reported that the number of ruptured tendons correlated with failure, with an odds ratio of 5.83 for three-tendon tears [ 13 ]. We consider that even a repaired tendon whose quality and excursion could be considered satisfactory is likely to fail when the concomitant SSC condition is worse because the SSC’s superior aspect and SSP’s anterior aspect are usually continuous [ 22 ].…”
Section: Discussionmentioning
confidence: 99%